Doctoral tuition scholarship from the Cyprus State Scholarships Foundation - Antoniou, Maria G. (My University, 2026)
My PhD student Nomiki Kallikazarou: Doctoral tuition scholarship from the Cyprus State Scholarships Foundation (2018-2019) valued at 4000 euros
Keywords: Sciences